Determinants Of Patient Satisfaction With The Quality Of Outpatient Services At West Pasaman Regional Hospital - Eva Yuhelmi; Bambang Setiaji (Sean Institute, 2024)
The results of the community satisfaction index (IKM) survey at West Pasaman Regional Hospital in 2022 were 75.99% (GOOD category) from the National Standard of 70%. However, patient complaints against hospitals increased greatly from the previous year. The aim of this research is to analyze the determinants of patient satisfaction with the quality of outpatient services at the West Pasaman Regional Hospital, West Pasaman Regency in 2023. The research method uses a Sequential Explanatory type, quantitative using a cross-sectional approach and qualitative using a phenomenological study approach carried out in December 2023 - February 2024, The sample was 97 people with sampling using accidental sampling and 8 informants. Data analysis using Chi Square Test and logistic regression test. Qualitative analysis was carried out using a triangulation process. Research Results The results of the Chi-Square statistical test of Reliability (0.016), Responsiveness (0.031), Assurance (0.049), Empathy (0.000), Tangibles (0.000), waiting time (0.000) concluded that there is a relationship between Reliability, Responsiveness, Assurance, Empathy, Tangibles and waiting time for patient satisfaction with outpatient services at West Pasaman District Hospital in 2023. Qualitative results of outpatient services are in accordance with hospital policies, health workers are responsive according to education and skills, all staff understand BPJS rules or other health services , Empathy outpatient services have been implemented, infrastructure is still lacking, such as inadequate seating, many patients are waiting because there are still patient statuses that have not been filled in, and it is indeed hampered by MR shortages, and the outpatient policy is in accordance with the SPM outpatient treatment at West Pasaman Regional Hospital, the staff must also be competent.